2015
DOI: 10.1002/tal.1256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grid curtains on the wind loads of a high-rise building

Abstract: Summary The effects of grid curtains on the local and overall wind loads of a high‐rise building are investigated in detail according to a series of wind pressure and wind force tests on rigid model in a wind tunnel. The effects of grid curtains on the mean and fluctuating wind pressures on windward and sideward walls when the wind direction is parallel to the geometrical axes are investigated, along with the effects of the most unfavorable wind pressures for all wind directions. Furthermore, the effects of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A Computational Fluid Dynamics (CFD) simulation conducted by Montazeri and Blocken also indicated that building balconies lead to significant changes in the wind pressure distribution on building surfaces because of flow separation and recirculation across the façade in multiple areas [8]. Quan et al reported that vertical ribs significantly decrease the most unfavorable suction coefficients in the corner recession regions and edge regions of façades [9]. Yuan et al used thin horizontal splitter plates to simulate appurtenance configurations and found that appurtenances can reduce the negative local peak pressure of the higher leading corner on a building's side face [10].…”
Section: Introductionmentioning
confidence: 99%
“…A Computational Fluid Dynamics (CFD) simulation conducted by Montazeri and Blocken also indicated that building balconies lead to significant changes in the wind pressure distribution on building surfaces because of flow separation and recirculation across the façade in multiple areas [8]. Quan et al reported that vertical ribs significantly decrease the most unfavorable suction coefficients in the corner recession regions and edge regions of façades [9]. Yuan et al used thin horizontal splitter plates to simulate appurtenance configurations and found that appurtenances can reduce the negative local peak pressure of the higher leading corner on a building's side face [10].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the number of sides, helix angles, chamfers and cut angles of a building can affect the response characteristics and aerodynamic performance of the building structure [2,3]. In addition, accessory structures on the building surface such as balconies [4][5][6], vertical panels [7], grid frames [8,9], solar panels [10,11], etc., can affect the surface wind pressure. Zheng et al [12] found that the presence of balconies increased the C p,avg on the windward and leeward sides by 5.2% and 8.9%, respectively, and the average wind speeds in the balcony space increased along the increasing of the balcony depth.…”
Section: Introductionmentioning
confidence: 99%